1989
DOI: 10.1111/j.1751-0813.1989.tb09781.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurological disease associated with degenerative axonopathy of neonatal Holstein‐Friesian calves

Abstract: The clinical and pathological features of 19 neonatal Holstein-Friesian calves affected with moderate to severe neurological disease are presented. Most calves were recumbent from birth, and many developed variable neurological signs including hyperaesthesia or depression, limb extension, head tremor, nystagmus, apparent blindness, and opisthotonos when stimulated. Consistent lesions of moderate to severe, diffuse, axonal swelling and loss, with Wallerian-type degeneration and myelin depletion in the spinal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…This is a lethal neurological disease in neonatal Holstein-Friesian calves caused by a deficiency in the urea cycle enzyme, argininosuccinate synthetase, that converts potentially toxic ammonia to urea, resulting in extreme elevation of citrulline and ammonia in plasma. 29 Citrullinaemia was widely disseminated throughout the Australian Holstein-Friesian population following importation of semen of the Canadian Holstein-Friesian bull Linmack Kriss King (LKK) 34 and diagnosis is based on elevated levels of citrulline (1-3 mmol/L) by day 3 or on a DNA-based test to detect the C→T mutation at nucleotide 258 in the gene coding for argininosuccinate synthetase, converting Arg86 into a termination codon. Lesions include mild to moderate diffuse astroglial swelling in the cerebrocortical grey matter, and mild to severe hepatocellular hydropic degeneration (Figure 6b).…”
Section: Holstein-friesianmentioning
confidence: 99%
“…This is a lethal neurological disease in neonatal Holstein-Friesian calves caused by a deficiency in the urea cycle enzyme, argininosuccinate synthetase, that converts potentially toxic ammonia to urea, resulting in extreme elevation of citrulline and ammonia in plasma. 29 Citrullinaemia was widely disseminated throughout the Australian Holstein-Friesian population following importation of semen of the Canadian Holstein-Friesian bull Linmack Kriss King (LKK) 34 and diagnosis is based on elevated levels of citrulline (1-3 mmol/L) by day 3 or on a DNA-based test to detect the C→T mutation at nucleotide 258 in the gene coding for argininosuccinate synthetase, converting Arg86 into a termination codon. Lesions include mild to moderate diffuse astroglial swelling in the cerebrocortical grey matter, and mild to severe hepatocellular hydropic degeneration (Figure 6b).…”
Section: Holstein-friesianmentioning
confidence: 99%
“…Similar syndromes are known in other breeds, including spinal dysmyelination of crossbred Brown Swiss calves, 3,4 degenerative axonopathy in Holstein‐Friesian calves, 2 weaver syndrome of Brown Swiss cattle, 5–10 and SMA in Brown Swiss, 11–13 horned Hereford, 14 Red Danish, 15 and Holstein Friesian calves 16 . These disorders are caused by genetic defects that lead to degenerative spinal cord disease.…”
mentioning
confidence: 68%
“…Several central nervous system (CNS) diseases in cattle have typical clinical features and are confined to specific breeds because of their genetic nature. Hereditary degenerative disorders of the CNS in calves include among others degenerative axonopathy, 2 spinal dysmyelination, 3,4 bovine progressive degenerative myeloencephalopathy (BPME or weaver syndrome), 5–10 and spinal muscular atrophy (SMA) 11–16 . The predominant clinical feature in the calf described here was moderate‐to‐severe spinal ataxia, leading to a tentative diagnosis of diffuse spinal cord disease with the most pronounced lesions in the segments between T3 and S3.…”
mentioning
confidence: 76%
“…A diffuse axonopathy in 19 Holstein-Friesian calves was previously described. 2 Affected animals had severe clinical deficits and most were recumbent from birth. Neuropathological studies showed a diffuse axonopathy, most pronounced in the spinal cord, with degeneration extending into spinal roots.…”
Section: Discussionmentioning
confidence: 99%